Gasification of High and Low Density Crop Residues - Singh Parihar, Amit Kumar; Kulkarni, Vinayak B.; Sridhar, G. (Journal of Technology Innovations in Renewable Energy, 2013)
Crop residue constitutes a large fraction of biomass particularly in agricultural based economies like India. The most abundantly generated crop residues are paddy husk, paddy straw, coconut shell, cotton stalk and sugar cane trash. It is estimated that the potential of power generation using crop residue is close to 14 GWe in a country like India. Even though the potential is large, the main drawback with crop residue is that it is sparsely distributed and being of low density causes collection and transportation problem. This drawback could be converted into an advantage by adopting distributed power generation technologies. The distributed power generation would fare well in the power range of few hundred kilowatts and the most appropriate technology would be the biomass gasification technology. Among the biomass gasification technologies, the downdraft technology is ideally suited for power generation. The downdraft technology is proven with solid or woody biomass, whereas there are limitations in terms of acceptance of all types of crop residues. In this paper, performance study of two vastly differing crop residues, namely coconut shell and cotton stalk has been discussed; both the feedstocks have been tested in “post-harvested” condition with minimum amount of pre-processing. The performance with cotton stalk was found to be comparable at part load; however at higher load the gas composition deteriorated due to poor material movement within the reactor. This had implication in terms of maximum power generated. There was loss of power to an extent of 12%. The operational issues with post-harvested cotton stalk has been brought out which are based on detailed measurements.